UPAYA PENINGKATAN KESELAMATAN PADA JALAN NASIONAL INDONESIA - Tjahjono, Tri (Jurnal Transportasi, 2016)
Abstract Indonesia faced serious challenges in improving traffic safety on the road. Government policy breakthrough has been made by issuing Presidential Decree No. 4 of 2013 of the Decade of Action for Road Safety 2011-2020 which is also in line with the National Road Safety Plan which was declared in 2011. Efforts to improve the safety of roads have been initiated through the road worthiness test. However, the results are generally conditionally accepted and facts on the field indicate that the number of accidents is still high. This paper discusses efforts to improve road safety and strategies that should be done on a national road, by conducting a road safety audit based on traffic accident data obtained from the Integrated Road Safety Management System which is owned Korlantas and understand the anatomy of the existing accident and behavioral factors of the society along the road through an audit. A case study was conducted on the Java North Coast Corridor, between Subang and Indramayu of West Java. Keywords: road safety, national roads, accident anatomy, road operation Abstrak Indonesia menghadapi tantangan yang berat dalam meningkatkan keselamatan berlalulintas di Jalan. Terobosan kebijakan telah dilakukan pemerintah dengan menerbitkan Inpres No. 4 Tahun 2013 tentang Dekade Aksi Keselamatan Jalan 2011-2020 yang juga selaras dengan Rencana Umum Nasional Keselamatan Jalan yang dideklarasikan pada tahun 2011. Upaya peningkatan keselamatan di bidang jalan telah dirintis melalui uji laik fungsi jalan. Walaupun demikian hasil yang didapat umumnya adalah semuanya diterima dengan bersyarat dan fakta di lapangan menunjukkan bahwa kejadian kecelakaan masih tinggi. Makalah ini membahas upaya peningkatan keselamatan jalan dan strategi yang harus dilakukan pada jalan nasional, dengan melakukan audit keselamatan jalan berbasis data kecelakaan lalulintas yang didapat dari Integrated Road Safety Management System yang dimiliki Korlantas serta memahami anatomi kecelakaan yang ada dan faktor perilaku masyarakat sepanjang jalan yang dilakukan audit. Kasus studi dilakukan pada jalur pantai utara Pulau Jawa di Kabupaten Subang dan Indramayu, Jawa Barat. Kata-kata kunci: keselamatan jalan, jalan nasional, anatomi kecelakaan, pengoperasian jalan